Analisis Dampak Pengaturan Perjanjian Kerja dalam Undang-Undang Cipta Kerja terhadap Keadilan Sosial - Pomolango, Syahidna; Sri Rejeki, Anggun; Moonti, Roy Marthen (Amandemen: Jurnal Ilmu pertahanan, Politik dan Hukum Indonesia, 2025)
The recent labor regulation reform through the Job Creation Law (Undang-Undang Cipta Kerja) has introduced new dynamics in regulating Fixed-Term Employment Agreements (PKWT), impacting social justice in Indonesia. This study aims to analyze the effects of PKWT regulation within the Job Creation Law on the principle of social justice, particularly in the context of Indonesia’s Asta Cita 4, which emphasizes protection for the entire nation. Employing a qualitative approach through literature review, the study systematically examines relevant laws, academic works, and related research. The findings indicate that although the law enhances labor market flexibility, the resulting legal uncertainty for fixed-term workers risks social inequality that contradicts the ideals of social justice. This research underscores the need for legislative reforms that prioritize worker protection and social security to align labor regulations with national aspirations embodied in Asta Cita 4. The implications provide recommendations for policymakers and future researchers to develop more empirical and in-depth studies to strengthen labor protections going forward.